Understanding students compulsive buying of apparel: an empirical study - Nor Asiah Omar,; Che Aniza Che Wel,; Syed Shah Alam,; Muhamad Azrin Nazri, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
Most compulsive buyers tend to be highly interested in fashion as well as their physical appearance and attractiveness. This study aims to investigate the impact of depression, materialism, excessive internet usage on compulsive buying behaviour among university students in buying apparels. A total of 177 questionnaires were collected via convenience sampling from university students located at Klang Valley. It is found that, depression and materialism are having a significant impact to compulsive buying behaviour. These findings will appeal to those interested in consumer behaviour in buying apparel.